2022
DOI: 10.1515/ract-2022-0084
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of graphene oxide/alginate and application of central composite design in the adsorption of Th(IV) on the nanobiocomposites

Abstract: In this study, graphene oxide and aginate were used to synthesis of nanobiocomposites under different synthesis conditions and the used to investigate the adsorption properties of Th (IV) ions from aqueous solutions. BET surface area, SEM and TEM images, FT-IR spectrometry, XRD techniques were used for the characterization of the adsorbents. In batch adsorption experiments, parameters affecting the adsorption efficiency such as solution pH, contact time, Th (IV) concentration and temperature were investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…200 3.3.4 Other radionuclides. Apart from the above radionuclides, various graphene-bearing composites have recently been used to remove other radionuclides, such as Th(IV), [202][203][204][205][206] Am(III), 33 and Eu(III). 33,201 For instance, Huang et al reported on the high adsorption capacity (220 mg g −1 at pH 3.0) and selectivity (∼100%, Fig.…”
Section: Cs(i)mentioning
confidence: 99%
“…200 3.3.4 Other radionuclides. Apart from the above radionuclides, various graphene-bearing composites have recently been used to remove other radionuclides, such as Th(IV), [202][203][204][205][206] Am(III), 33 and Eu(III). 33,201 For instance, Huang et al reported on the high adsorption capacity (220 mg g −1 at pH 3.0) and selectivity (∼100%, Fig.…”
Section: Cs(i)mentioning
confidence: 99%